Microbial Contamination of Peeled Oranges Sold Along Roadsides in Rumuolumeni, Port Harcourt, Rivers State, Nigeria - Amadi-Ikpa, C.N.; Dimkpa, F. B. (ANTIS PUBLISHER, 2024)
Microbial contamination of peeled oranges for sale were investigated vis-à-vis the microbial air quality at the points of sale. Sixty (60) oranges were purchased from high, low and less vehicular /human traffic sales points and analyzed using standard microbiological procedures. Analysis involved the spread plate and plate exposure techniques. Results of the analysis showed that the mean total microbial (bacteria and fungi) load on the surface of peeled oranges at the points of sale were: 1.0 x 104, 1.4 x 104, 1.4 x 104cfu/ml for less, low, and high human and vehicular movement sales points respectively, which showed no significant difference existed at (P>0.05) the points of sale. Basically, the microbial counts of 1.5 x 103, 2.7 x 103, 1.8 x 103 and 6.4 x 103cfu/ml were obtained for Escherichia coli, Staphylococcus aureus, Salmonella and heterotrophic bacteria respectively on the peeled orange surfaces, which showed a significant difference (P > 0.05) exist within the microbes. Pearson’s correlation coefficient showed 33% and 55% for bacterial and fungal spores on the peeled orange surfaces respectively, were dependent on time. A total of 29 microbial isolates belonging to five species (Escherichia, Staphylococcus, Salmonella, Candida and Aspergillus) were identified. The result showed that the outer surfaces of peeled oranges were contaminated with microbes of medical importance irrespective of the points of sale. Escherichia coli, Salmonella and Staphylococcus aureus counts satisfied the set limit of bacteria in ready-to-eat foods. However, the presence of these bacteria is an indicator of poor sanitary practices of orange vendors and polluted air quality at the sales point. Hence, orange vendors should receive appropriate training in hygiene matters that are in line with their work ethics and they should cover the peeled oranges displayed for sale.